ANALISIS STRATEGI PENGEMBANGAN BISNIS MENGGUNAKAN ANALISIS SWOT DAN QSPM - Panggabean, Agilina; Sumiati, Sumiati (Jurnal Kewirausahaan dan Inovasi, 2022)
Currently the world has depended on the internet which is supported by the development of science and technology. The development of science and technology is enough to bring considereble changes in all lines of people’s lives. One of the result of the development of science and techonology is the internet. Galsveme.Net requires best strategic management in developing its business. The formulation of a suitable strategy for Galsveme.Net is carried out in three stages, the first strage is the the input stage using the IFE Matrix and EFE Matrix. The secind stages is the matching stage using the SWOT Matrix and the Internal-External Matrix. The third stage is the decision stage using the QSP Matrix. At the matching strategy, the recommended strategy through the SWOT Matrix is patnership with UMKM who sell food and beverages to expand the previously mini canteen. In the analysis using the IE Matrix, the recommended alternative strategy is a market penatration strategy and/ or product development. At the decision stage with the QSPM, the two alternative strategies were chosen with the highest weight, namely market penatration strategy and/ or product development with a TAS (Total Attractiveness Score) of 5,42. manner.